The chromosome 3q26 OncCassette: A multigenic driver of human cancer. (January 2016) - Fields, Alan P.; Justilien, Verline; Murray, Nicole R.
Abstract: Recurrent copy number variations (CNVs) are genetic alterations commonly observed in human tumors. One of the most frequent CNVs in human tumors involves copy number gains (CNGs) at chromosome 3q26, which is estimated to occur in >20% of human tumors. The high prevalence and frequent occurrence of 3q26 CNG suggest that it drives the biology of tumors harboring this genetic alteration. The chromosomal region subject to CNG (the 3q26 amplicon) spans from chromosome 3q26 to q29, a region containing ∼200 protein-encoding genes. The large number of genes within the amplicon makes it difficult to identify relevant oncogenic target(s). Whereas a number of genes in this region have been linked to the transformed phenotype, recent studies indicate a high level of cooperativity among a subset of frequently amplified 3q26 genes. Here we use a novel bioinformatics approach to identify potential driver genes within the recurrent 3q26 amplicon in lung squamous cell carcinoma (LSCC). Our analysis reveals a set of 35 3q26 amplicon genes that are coordinately amplified and overexpressed in human LSCC tumors, and that also map to a major LSCC susceptibility locus identified on mouse chromosome 3 that is syntenic with human chromosome 3q26. Pathway analysis reveals that 21 of these genes exist within a single predicted network module. Four 3q26 genes, SOX2, ECT2, PRKCI and PI3KCA occupy the hub of this network module and serve as nodal genes around which the network is organized. Integration of available genetic, genomic, biochemical and functional data demonstrates that SOX2, ECT2, PRKCI and PIK3CA are cooperating oncogenes that function within an integrated cell signaling network that drives a highly aggressive, stem-like phenotype in LSCC tumors harboring 3q26 amplification. Based on the high level of genomic, genetic, biochemical and functional integration amongst these 4 3q26 nodal genes, we propose that they are the key oncogenic targets of the 3q26 amplicon and together define a "3q26 OncCassette" that mediates 3q26 CNG-driven tumorigenesis. Genomic analysis indicates that the 3q26 OncCassette also operates in other major tumor types that exhibit frequent 3q26 CNGs, including head and neck squamous cell carcinoma (HNSCC), ovarian serous cancer and cervical cancer. Finally, we discuss how the 3q26 OncCassette represents a tractable target for development of novel therapeutic intervention strategies that hold promise for improving treatment of 3q26-driven cancers.